2018
DOI: 10.1563/aaid-joi-d-17-00240
|View full text |Cite
|
Sign up to set email alerts
|

Does the Intake of Selective Serotonin Reuptake Inhibitors Negatively Affect Dental Implant Osseointegration? A Retrospective Study

Abstract: The success of osseointegration is influenced by several factors that affect bone metabolism and by certain systemic medications. Selective serotonin reuptake inhibitors (SSRIs) have been previously suggested to be among these medications. This study aims to investigate the association between systemic intake of SSRIs and failure of osseointegration in patients rehabilitated with dental implants. A retrospective cohort study was conducted, including a total of 2055 osseointegrated dental implants in 631 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…Preclinical and clinical evidence suggest that antidepressant intake may compromise bone metabolism and interfere with implant osseointegration 19,25‒29,33‒35 . Our current study demonstrated that the frequency of implant failure was significantly higher in antidepressant users (13.9%) than in non‐users (3.9%) (Table 3).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Preclinical and clinical evidence suggest that antidepressant intake may compromise bone metabolism and interfere with implant osseointegration 19,25‒29,33‒35 . Our current study demonstrated that the frequency of implant failure was significantly higher in antidepressant users (13.9%) than in non‐users (3.9%) (Table 3).…”
Section: Discussionsupporting
confidence: 50%
“…Some classes of antidepressants, such as SSRI, SNRI, and TCA, were associated with bone turnover and fractures in clinical reports 21‒24 . Recently, some studies demonstrated that the administration of antidepressants might increase the risk of dental implant failure 25‒29 . However, existing literature examining the link between antidepressants and implant failure largely focuses on the SSRI class, and, surprisingly, includes users of SNRI, such as venlafaxine, as being SSRI users.…”
Section: Introductionmentioning
confidence: 99%
“…Some systemic medications have been associated with a decrease in implant success through a decrease in osseointegration. Both selective serotonin reuptake inhibitors (SSRIs) and Proton Pump Inhibitors (PPIs) have been associated with increased implant failure rates 32‐35 . Both of these medications have non‐therapeutic effects on osteoblast differentiation and function and have been associated with decreased bone mineral density 36‐38 .…”
Section: Biologic Risk Factorsmentioning
confidence: 99%
“…Both of these medications have non‐therapeutic effects on osteoblast differentiation and function and have been associated with decreased bone mineral density 36‐38 . Patients taking SSRIs were approximately three times more likely to experience implant failures compared to individuals who were not taking SSRI medications 32,33 . Similarly, individuals taking PPIs demonstrated 2 to 3 times the failure rates of those who were not taking these medications 34,35 .…”
Section: Biologic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation